APLIKASI UP-KATALOG BERBASIS DIGITAL DALAM BRANDING PRODUK SANTRI SMK ROUDLOTUL MUBTADIIN - Ahmad Edi Yahya; Indra Kurniawan (Journal of Information System and Computer, 2024)
SMK Roudlotul Mubtadiin is a Vocational School under the auspices of the Roudlotul Mubtadiin Balekambang Foundation. SMK Roudlotul Mubtadiin has 6 Vocational Competencies and in each Vocational Competency, there is a Production Unit that has produced many products. Currently, SMK Roudlotul Mubtadiin still uses information media in the form of printed catalogs and through existing exhibition events in promoting and marketing products, this method often causes problems and is considered less effective and efficient in conveying information about products and consuming a lot of budget, therefore a digital-based product catalog application is needed to help solve the problems that exist, as well as increase competitiveness and also optimal service and provide detailed information on the products offered. The researcher designed a digital-based product catalog application in the form of a website using the prototype method which aims to provide input to the running system and produce a better system where the system is designed with the PHP programming language with the Laravel Framework and uses the MySQL Database. With the designed system, it will produce product catalog information and can make it easier for SMK Roudlotul Mubtadiin to introduce or brand the products that have been produced quickly and effectively.